The Influence of Parental Motivation on Students' Guitar Learning Outcomes at Percik Music School - Satria Manggala Kusumah; Yudi Sukmayadi (Universitas Muhammadiyah Enrekang, 2025)
This study aims to examine the influence of parental motivation on students' guitar learning outcomes at the Percik Music School. The background of this research is based on the important role parents play in supporting children's learning processes, particularly in the context of non-formal music education such as guitar courses. Although many studies have shown that parental motivation significantly contributes to academic achievement, few have specifically investigated this relationship within private instrumental music learning. This study employs a quantitative approach with a correlational research design. The sample consists of 35 students and their parents who actively participate in the guitar learning program. The instruments used include a parental motivation questionnaire and documentation of students' learning outcome scores. The data were analyzed using classical assumption tests, Pearson correlation, and simple linear regression. The results of the classical assumption tests indicate that the data are normally distributed, free from heteroscedasticity, and meet the linearity assumption. However, the Pearson correlation test results show no significant relationship between parental motivation and students' guitar learning outcomes (r = -0.207; p = 0.290). The regression results also indicate that parental motivation does not have a significant effect on learning outcomes (p = 0.290). These findings suggest that other factors, such as students’ intrinsic motivation, frequency of independent practice, or the quality of instruction, play a greater role in determining guitar learning outcomes. Therefore, effective guitar learning should not rely solely on parental support but also aim to strengthen students' internal motivation and active engagement in the music learning process.